Synthesis and characterization of silver nanoparticles loaded with carboplatin as a potential antimicrobial and cancer therapy - Tunç, Tutku (Cancer nanotechnology, 2024)
In recent studies with silver nanoparticles, it has been reported that the use of nanoparticles in carrier drug systems increases tumor suppression and reduces drug-related side effects. At the same time, the combination of traditional medicine with nanotechnology provides the opportunity to develop new antimicrobial agents. The aim of this study was to determine the anticancer, antimicrobial activities and pro-apoptotic effects of silver nanoparticles (AgNPs), and carboplatin-loaded silver nanoparticles (AgNPs-Car). Characterization studies of the synthesized nanoparticles were carried out by DLS, EDX-STEM, and FTIR analysis. The antiproliferative and pro-apoptotic effects of these molecules were evaluated using XTT and Annexin V, respectively. MIC (Minimum Inhibitory Concentration) test was used to determine the antimicrobial activity. The anticancer activity of the AgNPs-Car was high in MCF-7 (human breast adenocarcinoma), A549 (human lung carcinoma), and C6 (brain glioma) cells. The cell group with the most effective selective cytotoxic activity was C6 cells. It was also shown that AgNPs-Car and AgNPs induced DNA fragmentation eventually increasing apoptosis of cells. The antimicrobial activity of AgNPs and AgNPs-Car was evaluated on Gram-positive and Gram-negative pathogenic microorganisms and yeast fungi. Among the nanomaterials that reached effective MIC values according to reference sources, AgNPs-Car achieved better results. As a result, AgNPs-Car was found to be very successful in targeting C6 glioma cells by facilitating cell entry of the drug. In addition, their anticancer activity on MCF-7 and A549 cells was high and their toxicity was low. Silver nanoparticles are preferred for creating a better drug carrier system because of their qualitative properties and effects. Therefore, it is an interesting field for research on targeting cancer cells and pathogenic microorganisms.